The Entomological Collection of Thomas Say - Jonathan R. Mawdsley (Psyche: A Journal of Entomology)
The 770 remaining specimens of the entomological collection of Thomas Say presently housed in the Museum of Comparative Zoology are catalogued for the first time, including 71 specimens representing 56 species described by Say which are labelled in Say's handwriting and which are probably those specimens on which Say's species descriptions were based. The history of the Say entomological collection is recounted. Based on signatures on labels in the present Say collection material, it is apparent that Say exchanged specimens with many European entomologists, including Dupont, Germar, Laporte de Castelnau, Motschulsky, Schoenherr, Sturm, and Wiedemann. A protocol for the designation of Say lectotypes and neotypes is proposed.